Desain Akad Muamalah Perbankan Syariah Pada Ekonomi Islam - Abdul Rosid Siregar; Yasir Yasir; Sugianto Sugianto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Academic reconstruction is crucial to developing a more dynamic and innovative Sharia banking product that can compete with current conventional banking products. The aim of this study is to study the legal basis, structure, and implementation of this multi-barrier in the sharia banking business.In this study, library research methods are used. The data sources used consist of books and other relevant sources, such as DSN MUI fatwa related to this research topic. The results of the research showed that al-jam'u bainal uqud or multi akad was a major advance in the development of sharia banking products. This is a new discipline that has never been discussed in classical fiction books. As long as these multi-acts do not violate Islamic principles and values, the scholars give permission. The purpose of this multi-acade is to clarify rights and duties and to prevent iniquity, which will benefit mankind both in this world and in the Hereafter. In the product of mutanaqishah (MMq), there are many obstacles, such as syirkah, ijarah, and sale; in the history of muntahiyah bit-tamlik (IMBT), there is wa'd (promises), ijarah and sale, and both form a single product. There is a ta'alluq between these akad-akad and each other.